2020
DOI: 10.1111/are.14765
|View full text |Cite
|
Sign up to set email alerts
|

How cultured pearls acquire their colour

Abstract: Round nucleated pearls are produced through a surgical operation, where a round nucleus and a mantle tissue ‘saibo’ from donor oyster are inserted into the gonad of the host oyster. The epithelial cells in the mantle tissue proliferate around the nucleus, and thus, the pearl sac is formed. Pearl sac secrets nacre and forms a pearl. The quality and economic value of pearls are assessed by pearl features such as colour, brightness, lustre and shape. Among all these features, colour has been reported as an import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Many studies have demonstrated that the shell color of mollusks is generally attributable to the presence of biological pigments ( Wang et al, 2020 ). Indeed, yellow color components suspected to be carotenoids have been examined in cultured Akoya gold pearls ( Williams, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have demonstrated that the shell color of mollusks is generally attributable to the presence of biological pigments ( Wang et al, 2020 ). Indeed, yellow color components suspected to be carotenoids have been examined in cultured Akoya gold pearls ( Williams, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted to reveal the mechanisms of shell color formation and have identified multiple factors, involved in environmental factors and genetic factors, which contribute to the variability of mollusk shell color. In general, shell color is associated with the presence of shell pigments, mainly melanin, carotenoids, porphyrins, and bile pigments ( Wang et al, 2020 ). The striking color range of some gem-producing Mollusca, such as pearl oysters, has also attracted attention ( Williams, 2017 ), color in pearl oysters is of importance for pearl production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these Edison pearls exhibit intense bodycolors in the three main hue categories: purple, pink, and orange. These pearl colors are affected predominantly by the donor oyster's nacre color, which has been known to be genetically determined and inherited (McGinty et al, 2010;Karampelas and Lombard, 2013;Ky et al, 2014;Wang et al, 2020). For freshwater pearls, it is also known that polyenic pigments (such as unmethylated and partially methylated polyenes) containing various chain lengths of alternating double and single carbon-carbon bonds are responsible for color appearance (Soldati et al, 2008a;Karampelas et al, 2007Karampelas et al, , 2009Karampelas et al, , 2019a.…”
Section: Discussionmentioning
confidence: 99%
“…In North America and Europe, intense ‘pearl fishing’ over the past century has led to a steep decline and even extirpations of unionid populations but is now largely banned (Bauer, 1988; Anthony & Downing, 2001; Strack, 2015). Freshwater pearl culture for ornamental purposes is an important economy especially in China and other parts of Asia (Janakiram, 2003; Fiske & Shepherd, 2007), with considerable ongoing research efforts aimed at optimising the culture of high‐quality pearls and nacre (Wang et al ., 2020). Finally, live FBs are commonly used in the ornamental pet trade (Erdoğan & Erdoğan, 2015; Ng et al ., 2016).…”
Section: Cultural Ecosystem Servicesmentioning
confidence: 99%